Roles of Oxygen and Hydrogen in Crystal Orientation Transition of Copper Foils for High-Quality Graphene Growth - Hu, Junxiong (Sci Rep, 2017)
The high-quality graphene film can be grown on single-crystal Cu substrate by seamlessly stitching the aligned graphene domains. The roles of O(2) and H(2) have been intensively studied in the graphene growth kinetics, including lowering the nucleation sites and tailoring the domain structures. However, how the O(2) and H(2) influence Cu orientations during recrystallization prior to growing graphene, still remains unclear. Here we report that the oxidation of Cu surface tends to stabilize the Cu(001) orientation while impedes the evolution of Cu(111) single domain during annealing process. The crystal orientation-controlled synthesis of aligned graphene seeds is further realized on the long-range ordered Cu(111) substrate. With decreasing the thickness of oxide layer on Cu surface by introducing H(2), the Cu(001) orientation changes into Cu(111) orientation. Meanwhile, the average domain size of Cu foils is increased from 50 μm to larger than 1000 μm. The density functional theory calculations reveal that the oxygen increases the energy barrier for Cu(111) surface and makes O/Cu(001) more stable than O/Cu(111) structure. Our work can be helpful for revealing the roles of O(2) and H(2) in controlling the formation of Cu single-crystal substrate as well as in growing high-quality graphene films.